Primary Sclerosing Cholangitis and Psychological Wellbeing: A Scoping Review - Ranieri, Veronica; McKay, Kathy; Walmsley, Martine; Senior, Robert; Thorburn, Douglas; Kennedy, Eilis (Seminars in Liver Disease, 2019)
Primary sclerosing cholangitis (PSC) is a chronic liver disease resulting from the inflammation and scarring of an individual's hepatic bile ducts. With no curative treatment available and a risk of potentially severe complications and death, it is likely that those diagnosed with the illness may experience impairments in their psychological wellbeing. The aim of this scoping review is to locate, chart, and summarize all available literature on how PSC affects mental health and psychological wellbeing, as well as the factors that may or may not impact on the psychological wellbeing of those who have this diagnosis. This exercise identified five key themes within the literature: prevalence and characteristics of mental health problems, quality of life, unmet needs, medical treatment, and biomarkers. Three key recommendations for clinical practice emerge from this review.
Keywords: primary sclerosing cholangitis; mental health; psychological wellbeing; scoping review